More justice, more peace when peacemakers are advocates - Terry, Susanne, 1937- (ACR practitioner's guide series, 2020)
"More Justice, More Peace: When Peacemakers are Advocates is an attempt to broaden the vision of those practitioners with a passion for bringing about necessary change in our society who also work to bring people together to explore issues, solve problems, and overcome differences"--